Learning Affordances in Integrating Content and English as a Lingua Franca (‘ICELF’): on an Implicit Approach to English Medium Teaching - Smit, Ute (Journal of Academic Writing, 2013)
This contribution focuses on classroom discourse, and student evaluations thereof, in a specific tertiary EMT (English-medium teaching) setting. This is done by drawing on a rich, triangulated and longitudinal data base, comprising classroom interactional and ethnographic data that cover the whole duration of an international, four-semester English-medium hotel management programme (HMP) set in Vienna, Austria. On the basis of the discursive nature of learning it is argued that, in spite of the absence of any explicit language learning aims, the classroom discourse affords (language) learning spanning the functions of English as language for international hospitality purposes and of English as the lingua franca of the HMP community. Building on the recent discussions of EMT instructional types and of English used as a lingua franca in the international classroom, it is argued that the HMP represents a case of ‘implicit ICELF (integrating content and English as a lingua franca)'.